2021
DOI: 10.1186/s12891-021-04770-z
|View full text |Cite
|
Sign up to set email alerts
|

Incisional paresthesia following clavicle plate fixation: does it matter to patients?

Abstract: Background Operative management of clavicle fractures is increasingly common. In the context of explaining the risks and benefits of surgery, understanding the impact of incisional numbness as it relates to the patient experience is key to shared decision making. This study aims to determine the prevalence, extent, and recovery of sensory changes associated with supraclavicular nerve injury after open reduction and plate internal fixation of middle or lateral clavicle shaft fractures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Some authors believe that it can be sacrificed when necessary [ 9 ]. A 2021 retrospective study demonstrated that although patients may experience some improvement of paresthesia, most experience persistent symptoms [ 10 ]. Only a few studies have compared nerve-sparing and nerve-sacrificing techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors believe that it can be sacrificed when necessary [ 9 ]. A 2021 retrospective study demonstrated that although patients may experience some improvement of paresthesia, most experience persistent symptoms [ 10 ]. Only a few studies have compared nerve-sparing and nerve-sacrificing techniques.…”
Section: Discussionmentioning
confidence: 99%